The Role of Cholesterol in Biological Membranes - Michael Shoikhedbrod (International Journal of Cell Biology and Cellular Functions, 2023)
Cholesterol plays the role of a regulator that ensures the correct packaging of the lipid part of the membrane, which is necessary for its normal operation, by influencing on the mobility of the fatty acid tails of membrane lipids: if the membrane is too rigid and there is a danger of "freezing" of fatty acid chains, cholesterol causes it to liquefy, since the chains in its presence become more mobile; if the membrane is too “liquid”, then cholesterol thickens it. Some authors explain the sealing effect of cholesterol by the fact that in the presence of cholesterol, the slope of hydrocarbon phospholipid tails, which are located not perpendicular to the membrane plane, but at a certain angle, becomes smaller. Cholesterol increases the elasticity and mechanical strength of the bilayer, due to which the membrane can change its shape in response to the force applied to it. Cholesterol also regulates the permeability of cell membranes. At temperatures above the phase transition of phospholipids, cholesterol has a condensing effect (a decrease in the area occupied by a phospholipid molecule), reduces the rate of diffusion of phospholipids in the bilayer, and reduces the permeability of the bilayer for water molecules and ions. At temperatures below the phase transition of phospholipids, cholesterol increases the area occupied by the phospholipid molecule, increases the rate of diffusion of phospholipids in the bilayer, and increases the permeability of the bilayer for water molecules and ions. The article presents the physical interpretation of the properties of cholesterol, which play a vital role in biological membranes. It will be shown that the cholesterol of a biological membrane, placed in a solution of a negatively charged catholyte, sharply increases the permeability of the bilayer for water molecules and ions through cholesterol by increasing the electrical potential of bipolar phospholipids, which contributes to the adoption by cholesterol of a configuration with open gaps between its monolayers, which accelerates metabolic processes in the cell, leading to its rapid reproduction. It also will be shown that cancer cell membrane cholesterol, placed in an aqueous solution of a positively charged anolyte, prevents the permeability of the bilayer for water molecules and ions through cholesterol by reducing the electric potential of bipolar phospholipids to zero, which contributes to the adoption by cholesterol of a configuration with gaps between its monolayers closed in relation to the environment, cupping the cancer cell and consequently to its death.
Keywords: Cholesterol; bilayer; biological membrane; catholyte solution (hydrogen water) of nutrient medium; phospholipids